Security, privacy, and forensics issues in big data - Joshi, R. C.; Gupta, Brij 1982- (IGI Global, 2020)
"This book focuses on the security, privacy, and forensics of big data. It also examines the principles, algorithms, challenges and applications related to the security, privacy, and forensics of big data"--